1980 COMPETITIVE MANUSCRIPT AWARD, The Impact of Regulation Controls: Firms' Response to the Foreign Corrupt Practices Act. - Maher, Michael W. (The Accounting Review, 1981)
Abstract ABSTRACT: This paper presents a conceptual and empirical analysis of the way in which coalitions of managers (i.e., firms) respond to regulation. The conceptual analysis provides a model of managerial behavior based on the assumption that these coalitions make cost/benefit analyses of activities in their self-interest. The model is used to develop hypothesized responses to the internal accounting control provision of the Foreign Corrupt Practices Act of 1977. These hypotheses, that the regulation would not directly affect the level of internal accounting controls, but would affect the expenditure of resources for efforts to "prove" compliance with the law, were generally supported by the empirical results.